Investigation of Afterthoughts through Art, Natural and Social Science My Self “After Thoughts” - Rahat, Rohail; Shereen, Rabia; Bilal Abid, Muhammad (Journal of World Science, 2022)
Introduction: This article explores afterthoughts on a canvas by depicting portraits of self and natural scenes. The portraits on the canvas are comprised of the reflection of clouds, the reflection of the inner self in water and landscape in the water, and the portrayal of clouds, sky, and trees. The objective of this study is to analyze the results of works of art that are related to the natural sciences and social self of a painter. Method: The nature of this research is analytical, as the discussion and analysis are purely interpreted according to social points of view. The portraits have been analyzed within the paradigms of the concept of afterthoughts. Some articles, books, and opinions related to my research have been used as secondary data to get a deep understanding of the topic. Result: The study further investigates how the portraits on the canvas reflect one's inner self, life story, and thoughts by getting influenced by natural scenes and sceneries, as these paintings are the amalgamation of a careful process of imagination and thinking about a particular scene. The portrayals on the canvas are depicted after an organized discerning and contemplation. Conclusion: the study concludes that the process of afterthoughts has immense significance in terms of the expressions of feelings, thoughts, and emotions of people because art is such a great and effective tool that can be used to paint someone's inner reality, mindset, and overall story of life.